Joint decisions on pricing and advertising of dominant manufacturer with different advantage strategies. (2nd July 2016) - Liu, Bin; Zhang, Rong
Abstract: This paper investigates the joint decisions of dominant manufacturer with different advantage strategies in a dual channel system, consisting of two competing manufacturers and one common retailer, when the weak manufacturer advertises goods first. We investigate which advantage strategy is better for the dominant manufacturer – the operation strategy, wholesale price advantage strategy or channel advantage strategy – to address advertising launched by the weak manufacturer. In additional, we analyse which advantage strategy is for the dominant manufacturer. It is demonstrated that the dominant manufacturer always benefits from any advantage strategy. In detail, when the advertising has been provided by any manufacturer, the channel advantage strategy with single advertising from the weak manufacturer is the best choice for the dominant manufacturer if the channel substitutability is lower; otherwise, the wholesale price advantage strategy with both advertising is the best.